2018
DOI: 10.3390/buildings8020021
|View full text |Cite
|
Sign up to set email alerts
|

Interval Estimations of Building Heating Energy Consumption using the Degree-Day Method and Fuzzy Numbers

Abstract: Abstract:The purpose of this paper is to propagate the input uncertainties of the degree-day method to estimate the building heating energy consumption as numerical intervals. While it is common to use average or expected values (e.g., Typical Meteorological Year) to address the input uncertainties, this practice can only yield the best estimates as single-point values without informing the possible range of variations. After classifying two types of uncertainty as weather variability and imprecision in the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…A typical household's carbon emission is 78% higher in Memphis than in San Diego [161]. Cheng and Li [162] found that household energy consumption is strongly related to heating degree days (HDDs). This relation between household energy consumption and HDDs is also reported in China, Japan, the USA, and Canada [163], Turkey [164], and France [165].…”
Section: Influential Factors On Household Energy Consumption and Co 2 Emissionsmentioning
confidence: 99%
“…A typical household's carbon emission is 78% higher in Memphis than in San Diego [161]. Cheng and Li [162] found that household energy consumption is strongly related to heating degree days (HDDs). This relation between household energy consumption and HDDs is also reported in China, Japan, the USA, and Canada [163], Turkey [164], and France [165].…”
Section: Influential Factors On Household Energy Consumption and Co 2 Emissionsmentioning
confidence: 99%
“…In general, daily average temperature values are used for the building energy planning (e.g., Matzarakis and Balafoutis, 2004, Christensen et al, 2006, Mourshed, 2016, Cheng and Li, 2018, including the heating system design parameters. Because of its common use, we also used daily temperature data for Budapest.…”
Section: Datamentioning
confidence: 99%
“…In Ref. [23] a new concept (infiltration degree-days (IDD)) was proposed, which added a weighting factor calculated from relative infiltration. Huang [24] correlated residential building heating and cooling loads with different climatic parameters based on hourly simulated data.…”
Section: Introductionmentioning
confidence: 99%